1990
DOI: 10.1063/1.346741
|View full text |Cite
|
Sign up to set email alerts
|

A transmission electron microscopy study of low-temperature reaction at the Co-Si interface

Abstract: An efficient preparation method, which provides wedge-shaped cross-section transmission electron microscopy samples, has been developed. It was then used to investigate the structure of as-deposited cobalt multilayers on silicon substrates by rf plasma sputtering. It was found that an extended reaction takes place between Co and Si probably during the deposition. The cobalt atoms react with the silicon substrate to form an amorphous silicide layer. When the deposited layer is <3 nm thick, it entirely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(33 citation statements)
references
References 11 publications
6
26
1
Order By: Relevance
“…Our observations refine the earlier picture because we observed simultaneous growth of the Co 2 Si layer and consumption of the Co and CoSi layers. Moreover, in all previous investigations [10][11][12][16][17][18][19][20][21] the kinetic exponents for the growth of CoSi and Co 2 Si phases were found to be 0.5. In contrast, we observed a very definite deviation from the parabolic growth law.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Our observations refine the earlier picture because we observed simultaneous growth of the Co 2 Si layer and consumption of the Co and CoSi layers. Moreover, in all previous investigations [10][11][12][16][17][18][19][20][21] the kinetic exponents for the growth of CoSi and Co 2 Si phases were found to be 0.5. In contrast, we observed a very definite deviation from the parabolic growth law.…”
Section: Discussionmentioning
confidence: 87%
“…Thin reaction layers can be observed at the Co/a-Si interfaces already in the as-deposited sample. According to the literature, [10][11][12] these are amorphous CoSi layers formed during the deposition. Bright-field TEM images, taken on a CoSi intermetallic layer deposited at 423 K onto NaCl, contained dark spots, indicating that the layer was partially amorphous.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most inter esting experimental investigations of the structural and magnetic properties have been reported for Fe/Si [7⎯11] and Co/Si [10][11][12][13][14][15][16][17][18][19] thin film systems. Analysis of the available data showed that the antiferromagnetic exchange between iron layers in Fe/Si/Fe systems was observed for silicon layer thicknesses within 1.4-1.7 and 1.4-2.2 nm (see, e.g., [20,21]).…”
mentioning
confidence: 99%